Pengaruh Kualitas Layanan terhadap Kepuasan Pasien dan Citra Institusi pada Rsud Kabupaten Wakatobi - Muhammad Syafaruddin, La Ode; Daulani, Ahmad (CV. Creative Tugu Pena, 2024)
The objectives of this research are: 1) Testing the influence of service quality on patient satisfaction at the Wakatobi District Hospital; 2) Testing the influence of patient satisfaction on the image of the institution at the Wakatobi District Hospital; 3) Testing the influence of service quality on the image of the institution at the Wakatobi Regency Regional Hospital; 4) Testing the influence of Patient Satisfaction as an intervening variable on Service Quality and Institutional Image at Wakatobi District Hospital. The population in this study were patients and families of patients at the Wakatobi District Hospital. The sample taken was determined to be 68 people. The sampling method used is purposive random sample, namely a sample selection technique based on certain criteria. The data collection technique used was a questionnaire. Data analysis techniques use descriptive analysis, validity testing, reliability testing, hypothesis testing and direct and indirect influence testing using the Structural Equation Modeling (SEM) concept with the Smart PLS (Partial Least Square) program. The result showed that: 1) Service quality has a significant positive effect on patient satisfaction at the Wakatobi district hospital, showing the original sample estimate value between the influence of service quality on satisfaction of 0.742 and a positive value. 2) Patient satisfaction has a significant positive effect on the image of the institution at the Wakatobi District Hospital. 3) Service quality has a significant positive effect on the image of the institution at the Wakatobi District Hospital. The calculated T-value of 1.727 is greater than the T-table of 1.668. 4) Patient Satisfaction as an intervening variable has a dominant influence on Service Quality and Institutional Image at the Wakatobi District Regional Hospital. Keywords: Learning Herbal Drink, Community Service, Community Business Opportunities